Crying laughing - Rubin, Lance, 1981- (Alfred A. Knopf, 2019)
Winnie Friedman has been waiting for the world to catch on to what she already knows: she's hilarious. It might be a long wait, though. After bombing a stand-up set at her own bat mitzvah, Winnie has kept her jokes to herself. Well, to herself and her dad, a former comedian and her inspiration. Then, on the second day of tenth grade, the funniest guy in school actually laughs at a comment she makes in the lunch line and asks her to join the improv troupe. Maybe he's even . . . flirting? Just when Winnie's ready to say yes to comedy again, her father reveals that he's been diagnosed with ALS. That is . . . not funny. Her dad's still making jokes, though, which feels like a good thing. And Winnie's prepared to be his straight man if that's what he wants. But is it what he needs? Caught up in a spiral of epically bad dates, bad news, and bad performances, Winnie's struggling to see the humor in it all. But finding a way to laugh is exactly what will see her through.